Comparison of Perinatal Outcomes of Letrozole-Induced Ovulation and Hormone Replacement Therapy Protocols in Patients With Abnormal Ovulation Undergoing Frozen-Thawed Embryo Transfer: A Propensity Score Matching Analysis - Zhang, Wenjuan; Liu, Zhaozhao; Zhang, Junwei; Ren, Bingnan; Liu, Manman; Li, Jiaheng; Zhang, Wen; Guan, Yichun (Frontiers in Endocrinology, 2022)
Background: With the increasing use of frozen embryo transfer (FET), the best endometrial preparation protocol is always discussed, but there is no unified conclusion for the population with abnormal ovulation. Most studies had observed pregnancy and pay less attention to perinatal outcomes, and the population heterogeneity was large, so they could not draw convincing conclusions. Methods: It was a retrospective cohort study with propensity score matching (PSM) analysis. The included population were patients who were undergoing FET cycles in the reproductive center of the Third Affiliated Hospital of Zhengzhou University from January 2016 to September 2020. The main outcome measures were Clinical pregnancy rate, live birth rate, very preterm delivery (VPTD), preterm delivery (PTD), low birth weight (LBW), macrosomia, small for gestational age (SGA), large for gestational age (LGA), hypertensive disorders of pregnancy (HDP), gestational diabetes mellitus (GDM), premature rupture of membrane (PROM), placenta previa, and congenital abnormality. Results:A total of 8010 women were enrolled. Due to the large heterogeneity among patients, we conducted 1:1 PSM, and 1461 women were matched in each group. Compared with the hormone replacement therapy (HRT) group, the letrozole-induced ovulation (L-OI) group had a smaller proportion of thin endometrium (27.38% vs. 41.07%) and thicker endometrium on the day of embryo transfer (9.63±1.82 vs. 8.91±1.38). There were no significant differences in the clinical pregnancy rate, early abortion rate or live birth rate between the two groups. There was no significant difference in perinatal outcomes of singleton live birth, including VPTD, PTD, postterm delivery, LBW, macrosomia, SGA, LGA, GDM, HDP, placenta previa, and congenital malformation. Conclusion: For people with abnormal ovulation, the pregnancy and perinatal outcomes of HRT and L-OI protocols are reassuring. It seems that both protocols are safe and effective for endometrial preparation in frozen-thawed embryo transfer in the clinic.